2011
DOI: 10.1108/02651331111167589
|View full text |Cite
|
Sign up to set email alerts
|

“What? I thought Samsung was Japanese”: accurate or not, perceived country of origin matters

Abstract: PurposeExtensive research has shown that country‐of‐origin (COO) information significantly affects product evaluations and buying behavior. Yet recently, a competing perspective has emerged suggesting that COO effects have been inflated in prior research and even that the COO concept has become irrelevant. The purpose of this paper is to reconcile these two competing perspectives by examining the effects of individual brand origin perceptions.Design/methodology/approachThe conceptual framework is grounded in c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
218
1
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(241 citation statements)
references
References 64 publications
14
218
1
8
Order By: Relevance
“…We decided to use real brands in order to provide to our sample real photos and a realistic and consistent positioning of the brands. This is also consistent with other previous research into COO effects (Ahmed et al, 2004;Magnusson et al, 2011). Furthermore, as stereotypes could be related to specific product categories, we chose three main categories and both typical and untypical Italian products: mass food products (Paluani and Pasta Zara), durable products (Giuliana Teso and Inglesina) and industrial products (Microline and Idrobase).…”
Section: Methods 41 Experiments Descriptionsupporting
confidence: 61%
See 1 more Smart Citation
“…We decided to use real brands in order to provide to our sample real photos and a realistic and consistent positioning of the brands. This is also consistent with other previous research into COO effects (Ahmed et al, 2004;Magnusson et al, 2011). Furthermore, as stereotypes could be related to specific product categories, we chose three main categories and both typical and untypical Italian products: mass food products (Paluani and Pasta Zara), durable products (Giuliana Teso and Inglesina) and industrial products (Microline and Idrobase).…”
Section: Methods 41 Experiments Descriptionsupporting
confidence: 61%
“…As highlighted by Bhaskaran & Sukumaran (2007), these contradictions could depend on the different contexts and methodologies that scholars have used in their studies. Recent research reveals that COO effects may not be as extensive as prior research has assumed (Magnusson et al, 2011). This result could depend both by the brand origin confusion and by the methodology.…”
Section: Literature Reviewmentioning
confidence: 78%
“…The firms can now understand the need of carefully choosing the right combinations among the available products attributes and can utilise accordingly. In the last research question about COO where Indian air conditioners were the most preferred, Japan was next, followed by South Korea, consumers associate a brand with a particular country and it drive their attitudes towards particular purchase decision (Magnusson et al, 2011). The reason of this outcome may be inclination of Indian consumer towards Indian manufacturing goods due to gradual but steady improvement in product quality (Motwani, 1994) and it is also observed that consumer of some state prefer local products over foreign (Bankole et al, 2014;Cui and Liu, 2001;Kwok et al, 2006;Zhu et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…However with globalisation COO information has become more indefinite and complicated to ascertain. Especially with hybrid products consumers still associate a brand with a particular country and these associations compel their attitudes toward the brand and finally pursue them to make purchase (Magnusson et al, 2011). Literature further asserts that consumers perception and evaluation about the products quality often takes reliance on its COO (Gurhan-Canli and Maheswaran, 2000;Hong et al, 1990;Li and Wyer, 1994;Maheswaran, 1994).…”
Section: Country Of Originmentioning
confidence: 99%
“…Firms from emerging markets are not known for having the most innovative technology, superior human capital, or worldwide-recognized brands. They may also experience shortages of financial capital, which attenuates the implementation of marketing strategies (Magnusson, Westjohn, & Zdravkovic, 2011;Wright, Filatotchev, Hoskisson, & Peng, 2005). In Latin American countries, several studies have demonstrated that the brand is seen by customers as a sign of product quality, assisting them to make their purchasing decisions (e.g., Hidalgo et al, 2007;Lopes, Garcia, Santos, & Schiavo, 2013;Manzur, Hidalgo, Olavarrieta, & Farías, 2005Merino & Gonzalez, 2008;Milberg & Sinn, 2008;Olavarrieta, Hidalgo, Manzur, & Farías, 2006Olavarrieta, Manzur, Hidalgo, & Farías, 2008;Rojas-Méndez, Erenchun-Podlech, & Silva-Olave, 2004;Torres, Hidalgo, & Farias, 2007;Zanette, Lourenço, & Brito, 2013).…”
Section: Conceptual Frameworkmentioning
confidence: 99%